How Commissives Depend on Representatives: An Illocutionary Analysis of Collective Identity in Zohran Mamdani’s Election Victory Speech - Dian Marisha Putri; Sari Gracya Laura Sianturi; Salwa Salsabillah; Amila Nirina Nasution; Maysa Lani (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Political victory speeches are strategic discursive tools used to build public legitimacy andconstruct political identity. This article investigates the linguistic strategies in ZohranMamdani’s 2025 mayoral victory speech, focusing on the interplay between representative andcommissive speech acts through John Searle’s pragmatic framework. Employing a descriptivequalitative method, this study analyzes how the speaker constructs collective agency and alignspolitical commitments with the United Nations Sustainable Development Goals (SDGs). Thefindings demonstrate that Mamdani utilizes representative acts as preparatory conditions tovest political ownership in the collective, which subsequently transforms commissive acts intocollectivized commitments. Furthermore, the analysis reveals a significant alignment betweenthese policies and SDG targets 11.1, 11.2, 3.8, and 16.5, suggesting that the speechperformatively enacts the participatory governance prescribed by SDG 16.7. This researchcontributes to the study of political pragmatics by highlighting the constitutive relationshipbetween speech acts, providing a framework for analyzing how discourse actively constructsthe collective agency necessary for democratic governance.Keywords: Sustainable Development Goals, Speech act theory, Illocutionary Act